Soutenir la justice épistémique par la formation réciproque au cœur d'initiatives citoyennes de transition énergétique porteuse de justice sociale - Laurence Brière; Guillaume Moreau; Maude Prud'homme; Isabel Orellana; Marie-Ève Marleau; Martine Chatelain
The eco-citizen movement for an energy transition is working to transform the dominant economic-energy system aiming for social justice and respect for the environment. Collaborating with the people engaged in this mobilization in the context of a participatory action-research, we have raised epistemic justice issues inherent to this political project. We also wanted to create spaces for reciprocal learning that would highlight the complementarity of different types of knowledge. We reflected on the crucial needs and possible vectors for intensifying collaboration and knowledge sharing between the different groups of actors that make up the movement: labor associations, environmental and community groups, citizen committees and academia. We have also proposed an innovative conceptual framework for energy justice that takes into account the very concrete realities of eco-citizen struggles and initiatives.